Dehydroepiandrosterone (DHEA) replacement decreases insulin resistance and lowers inflammatory cytokines in aging humans - Weiss, Edward P. (Impact Journals LLC, 2011)
Plasma dehydroepiandrosterone (DHEA) decreases ~80% between ages 25 and 75 yr. In a preliminary study, we found that 6 mo of DHEA replacement improved insulin action in elderly individuals. The purpose of the present larger, randomized double-blind study was to determine whether a longer period of DHEA replacement improves glucose tolerance. Fifty-seven men and 68 women aged 65 to 75 yr were randomly assigned to 50 mg DHEA or placebo once daily. Year one was a randomized, double blind trial. Year 2 was an open label continuation. DHEA replacement improved glucose tolerance in participants who had abnormal GT initially, reduced plasma triglycerides, and the inflammatory cytokines IL6 and TNFα. This trial was registered at clinicaltrials.gov as NCT00182975.